2018
DOI: 10.21475/ajcs.18.12.08.pne885
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of yam (Dioscorea spp.) landrace collections from Ethiopia using simple sequence repeat markers

Abstract: Yam (Dioscorea spp.) is an important root crop widely used for food, feed and industrial raw material. Knowledge on the genetic diversity present among yam genetic resources is fundamental for variety development and conservation strategies. The objectives of this study were to determine the magnitude and genetic relationship present among yam landrace collections using simple sequence repeat (SSR) markers and to identify genetically unique genotypes for efficient breeding and conservation. Thirty-three yam la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
3
18
2
Order By: Relevance
“…Finally, high levels of genetic diversity using ISSR markers were also reported by Nascimento et al (2013) and Kung et al (2016). Other studies using SSR (Otoo et al, 2015;Arnau et al, 2017;Mulualem et al, 2018) and AFLP markers (Rivera-Jiménez et al, 2011) also reported high genetic diversity in yam.…”
Section: Genetic Diversitymentioning
confidence: 55%
See 1 more Smart Citation
“…Finally, high levels of genetic diversity using ISSR markers were also reported by Nascimento et al (2013) and Kung et al (2016). Other studies using SSR (Otoo et al, 2015;Arnau et al, 2017;Mulualem et al, 2018) and AFLP markers (Rivera-Jiménez et al, 2011) also reported high genetic diversity in yam.…”
Section: Genetic Diversitymentioning
confidence: 55%
“…Assessing the genetic diversity of a plant species using molecular DNA markers is an important tool for cultivar identification, taxonomic and phylogenetic studies, genetic mapping, and germplasm management and conservation (Onda and Mochida, 2016). The genetic diversity of yam has been characterized using several markers, including RFLP (Mukherjee and Bhat, 2013), SSR (Arnau et al, 2017;Mulualem et al, 2018), AFLP (Rivera-Jiménez et al, 2011;Wendawek et al, 2013), ISSR (Kung et al, 2016;Ousmael et al, 2019), and SNP (Agre et al, 2019). Bhattacharjee et al (2018) constructed a genetic linkage map for D. alata based on 380 EST-SSR markers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the genotypes' clustering patterns did not correspond to the predefined population structure based on the collection regions. This may be because genotypes gathered from similar regions belong to the same gene pool or may have similar ancestral relationships [35]. Conversely, William et al [36] reported that genetic dissimilarity among test genotypes could arise due to the diverse ancestral origin, high gene flow caused by cross-pollination and possible gene or chromosomal mutation.…”
Section: Genetic Diversity and Population Structure Of Sesame Germplasm Based On Ssr Markersmentioning
confidence: 99%
“…Genetic diversity in D. rotundata has been assessed using morphological traits 8 , 9 , isozymes 10 , 11 , amplified fragment length polymorphism 12 , simple sequence repeats 13 , 14 , random amplified polymorphic DNA 15 and single nucleotide polymorphisms 16 . As a result of the strong environmental influence on their expression, phenotypic markers may not precisely capture the available diversity in a population 7 , 17 . Molecular markers, particularly SSR and SNPs have been widely employed to study the diversity in many species with much success, however, very low or negligible correlations have been reported between the dissimilarity matrices from the genotypic and phenotypic data 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%